INTERNATIONNAL CRIMINAL COURT: INSTRUMENT OF JUSTICE OR WESTERN IMPERIALISM ‒ DARFUR CASE STUDY - Babić, Danilo D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
This work analyzes the work of  International Criminal Court focusing on alleged Darfur genocide. We are trying to reassess allegations of African public which claim that ICC is biassed towards Africa, selective and implementing double standards. Further more they claim that the Court is, in fact, an instrument of new Western imperialism. The key moment which have broken the ICC-Africa relationship beyond repair is arrest warrant for Sudan president Omar Al Bashir. We are questioning the legality and legitimacy of that warrant. Моreover, in order to prove or deny the objectivity of the court we are analizing the financing of the ICC and its relationship with the NGO sector. We examine the effects of the court decisions on the peace and reconciliation in the region.